Retrospective Neuropathological Review of Prion Disease in UK Haemophilic Patients - Lee, Christine A.; Ironside, James W.; Bell, Jeanne E.; Giangrande, Paul; Ludlam, Christopher; Esiri, Margaret M.; McLaughlin, James E. (Thrombosis and Haemostasis, 1998)
In 1996, the CJD surveillance unit in Edinburgh, UK described nvCJD which was thought to be the human equivalent of bovine spongiform encephalopathy (BSE). The identification of prion protein in the tonsil of an affected individual has raised the question of transmission of nvCJD via blood products. This study examines the post mortem brains of 33 patients who were treated with clotting factor concentrate of predominately UK donor source during the years 1962-1995. The brains were examined by conventional histological methods and also for the prion protein using monoclonal antibodies KG9 and 3F4. No evidence of spongiform encephalopathy was found and the immunocytochemistry was negative for PrP in all cases. It is concluded that, at present, there is no evidence for the transmission of nvCJD via clotting factor concentrate to patients with haemophilia.